Nilai Budaya dalam Situs Pati Ayam sebagai Pelestarian Budaya Lokal Bagi Generasi Z - Fatimah Anisalikha; Laura Dewi Anggraini; Diva Mustika Utami; Luthfa Nugraheni (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
The Pati Ayam Site in Kudus Regency is one of the important cultural heritages that represents past civilization in Central Java. The purpose of this study is to explore the cultural values ​​contained in the Pati Ayam Site and the right approach to introduce it to Generation Z using the Systematic Literature Review (SLR) method, by reviewing various previous studies related to cultural preservation, involvement of the younger generation, and the potential of historical sites as educational media. The results of the study indicate that a social media-based approach and participatory activities can be an effective bridge in increasing awareness and involvement of Generation Z towards local cultural heritage. Thus, the preservation of the Pati Ayam Site is not only a form of historical conservation, but also a relevant educational tool for the current generation.